How functional value analysis unlocks the design paradox and will result in novel and cost-effective process engineering solutions - Jansen, J (Acta Structilia, 1998)
Functional Value Analysis involves identifying clearly what each of the individual elements of a venture, project, product or service actually do. It is directed towards analyzing the functions or objectives to improve value through the optimization of whole life cycle costs. Value is defined as the ratio between function required (no less, no more) and the cost of achieving it. It can be considered as a yardstick for achieving the completeness of a product.